External corporate leverage: Comparative comments among some latin american countries 2000-2014 - Cortez Cortez, Gaby (2016)
In this article we will analyze the movement of financial resources that target capital formation of companies in Peru during the period 2000-2014, as well as some countries in Latin America to make a comparison between them. In this sense the external debt of Peru, Brazil, Colombia and Mexico will be discussed, with emphasis on the development of private non-guaranteed debt, in order to determine their movement and representative instruments that have influenced its improvement.